Climatic, geomorphologic and hydrologic perturbations as drivers for mid‐ to late Holocene development of ice‐wedge polygons in the western Canadian Arctic. (2nd July 2018) - Wolter, J.; Lantuit, H.; Wetterich, S.; Rethemeyer, J.; Fritz, M.
Abstract: Ice‐wedge polygons are widespread periglacial features and influence landscape hydrology and carbon storage. The influence of climate and topography on polygon development is not entirely clear, however, giving high uncertainties to projections of permafrost development. We studied the mid‐ to late Holocene development of modern ice‐wedge polygon sites to explore drivers of change and reasons for long‐term stability. We analyzed organic carbon, total nitrogen, stable carbon isotopes, grain size composition and plant macrofossils in six cores from three polygons. We found that all sites developed from aquatic to wetland conditions. In the mid‐Holocene, shallow lakes and partly submerged ice‐wedge polygons existed at the studied sites. An erosional hiatus of ca 5000 years followed, and ice‐wedge polygons re‐initiated within the last millennium. Ice‐wedge melt and surface drying during the last century were linked to climatic warming. The influence of climate on ice‐wedge polygon development was outweighed by geomorphology during most of the late Holocene. Recent warming, however, caused ice‐wedge degradation at all sites. Our study showed that where waterlogged ground was maintained, low‐centered polygons persisted for millennia. Ice‐wedge melt and increased drainage through geomorphic disturbance, however, triggered conversion into high‐centered polygons and may lead to self‐enhancing degradation under continued warming.